The Relationship Between Learning Motivation And Emotional Intelligence On Student Learning Outcomes At SMK Negeri 1 Gunung Sahilan - Indah Wijayanti; Firman; Netrawati; Mohd Nazri Abdul Rahman (Quality : Journal Of Education, Arabic And Islamic Studies, 2024)
Learning outcomes are actual achievements displayed by children. Learning outcomes are abilities obtained after going through learning activities. In general, factors that can influence student learning achievement can be divided into two, namely internal factors and external factors. External factors are factors that arise from outside the student such as learning resources, learning facilities, school environment, teachers, friends, parents and others. Meanwhile, internal factors are factors that exist within students such as intelligence, talent, interest, motivation, physical condition, independence, physical fatigue and spiritual fatigue. In this research, the factors that will be investigated whether they have a big influence on student achievement are emotional intelligence and learning motivation. Learning motivation is a series of impulses or driving forces that come from within oneself and from outside to carry out learning activities to cause changes so that the goals desired by the learning subject can be achieved. Emotional intelligence can also support students' success in learning, so that emotional intelligence factors have an important role in learning.